College Students’ Learning Burnout: Concept, Structure, Status, Outcomes, and Influencing Factors - Hou Yongmei (An Overview of Literature, Language and Education Research Vol. 9, 2025)
Background: Learning burnout is a common behavioral problem among college students, which seriously affects their physical and mental health, restricts the improvement of talent cultivation quality in universities, and restricts the production efficiency of employers. Objective: The objective of the study is to understand the current research status of college students’ learning burnout and analyze its main advantages and disadvantages. Methods: A literature search was used, with "college students+learning burnout" as the keyword, to search for academic full-text literature (i.e. with abstracts, keywords, etc. that can obtain the full text). The literature sources included journals, dissertations, and conference papers from databases such as Web of Science, EBSCO, LISA, EI, ProQuest, IEEE, ACM, CNKI, Google, etc. Results: Sixty-three papers were included. Previous literature shows the following 3 points: First, the global incidence of learning burnout among college students is 38%. Second, learning burnout is one of the important indicators of teaching quality in universities, as well as the learning effectiveness and physical and mental health of college students. Finally, college students’ learning burnout is influenced by multiple factors, including social environment, school, family, social support, and personal factors. Conclusion: The academic community is increasingly concerned about the learning burnout of college students, but there is still no unified opinion on the concept, structure, and measurement tools, and research methods need to be improved.